2021
DOI: 10.1002/smsc.202000014
|View full text |Cite
|
Sign up to set email alerts
|

1/f Noise and Machine Intelligence in a Nonlinear Dopant Atom Network

Abstract: Noise exists in nearly all physical systems ranging from simple electronic devices such as transistors to complex systems such as neural networks. To understand a system's behavior, it is vital to know the origin of the noise and its characteristics. Recently, it was shown that the nonlinear electronic properties of a disordered dopant atom network in silicon can be exploited for efficiently executing classification tasks through "material learning." Here, we study the dopant network's intrinsic 1/f noise aris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 30 publications
(103 reference statements)
0
13
0
Order By: Relevance
“…The measured 1/f noise spectral density in Fig. 4d indicated that PdSe 2 photodetectors possess typical characteristics of 1/f noise, which can be determined by the Hooge's empirical relationship (𝑆𝑆 𝑙𝑙 = 𝐴𝐴 • 𝑖𝑖 𝛼𝛼 /𝑓𝑓 𝛽𝛽 ), 61,62 where i, f, A are the channel current, the frequency, and noise amplitude, respectively. Current noise induced by 1/f noise decreases gradually with the increasing applied frequency.…”
Section: Resultsmentioning
confidence: 92%
“…The measured 1/f noise spectral density in Fig. 4d indicated that PdSe 2 photodetectors possess typical characteristics of 1/f noise, which can be determined by the Hooge's empirical relationship (𝑆𝑆 𝑙𝑙 = 𝐴𝐴 • 𝑖𝑖 𝛼𝛼 /𝑓𝑓 𝛽𝛽 ), 61,62 where i, f, A are the channel current, the frequency, and noise amplitude, respectively. Current noise induced by 1/f noise decreases gradually with the increasing applied frequency.…”
Section: Resultsmentioning
confidence: 92%
“…Intrinsic electrical properties of this nature that are nonlinear with network wide high-dimensionality and obey the 1/f Îł power law of maximized information processing, and are manifested in a recurrently connected random network structure, have recently proven to play a key role in in-materio RC tasks of binary classification and prediction. [42,45,46] Thus, by utilizing the innate dynamics emergent from our SWNT/Por-POM reservoir, we proceeded to establish the RC benchmark tasks of waveform generation and object classification, which we present in the next sections.…”
Section: High-dimensional Reservoir States-lissajous Plotsmentioning
confidence: 99%
“…[ 14–16 ] One of the biggest challenges for material‐based computing is the control of the output by external stimuli, because materials exhibit dynamic fluctuations at all times. [ 17 ] Among the potential applications of different architectures of material‐based neural networks, reservoir computing (RC) is a promising avenue. [ 18 ] In RC, a randomly connected network, the “reservoir,” creates nonlinear projections of inputs into high‐dimensional space.…”
Section: Introductionmentioning
confidence: 99%